Strategic unionism and partnership : boxing or dancing? - Gregory, Denis; Huzzard, Tony, 1957-; Scott, Regan (Palgrave Macmillan, 2004)
"How do we understand 'social partnership'? How does partnership vary across Europe and beyond? What are the implications of partnership for union renewal? This book addresses these questions by exploring the relationship between union renewal and partnership in an international context. It focuses in particular on experiences of co-operative industrial relations, normally understood as 'social partnership', in eight countries. The authors introduce and develop the terms 'boxing' and 'dancing' as metaphors for adversarial and co-operative industrial relations, and then offer an in-depth investigation of 'dancing' as a trade union strategy. It is argued that effective unions will need to skilfully combine both boxing and dancing activities which are interdependent and not a trade-off."--BOOK JACKET.